(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
High blood pressure or hypertension is one of the most common diseases of the cardiovascular system today. The disease is manifested by an increase in arterial blood pressure, and often its indicator exceeds 140/90. According to many experts in the field of cardiovascular diseases, hypertension often occurs as a result of blood circulation disorders. Heart failure is also included in the list of its causes. This disease can trigger the development of secondary diseases in patients, for example, stroke, heart attack.